STRATEGI PROGRAMMING DALAM PENGEMASAN PROGRAM “HAFIZ INDONESIA 2015” RCTI UNTUK MEMPEROLEH RATING SHARE TINGGI - Kutanto, Haronas (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2017)
ABSTRACTThe aim of creation of the Hafiz program is to provide alternative displays for children. HafizIndonesia's television program features talented children in memorizing the Qur'an without anyscenarios or scripts. So the participants present themselves on the television screen as it is. Thepurpose of this research is to know the Planning Programming strategy and PackagingProgram of Hafiz Indonesia 2015 in RCTI, in order to get high share rating. This researchmethod is using qualitative and descriptive. The theory used is Fred Wibowo’s productionconcept. The results of programming strategy in production concept are (1) RCTI is strippingstrategy on big audience and checker boarding strategy when the number of audience isdecreasing, but RCTI also uses the strategy of tent poling to introduce new program. (2) Theplanning process of Hafiz Indonesia program is carried out in a mutual way, not only by theprogramming division, but starting from the analyst program. They are consisting ofprogramming divisions and other people who are members of the program committee. (3) Preproductionactivities will be aired and begun by casting ideas or ideas into an outlinecontaining an event's program. The selected resource is the person who has the credibility andknows exactly about the topic to be discussed. Theoretically, the result of this research isexpected to give a constrictive contribution to the development and assessment ofcommunication science generally and practically, it is expected to be input for interestedparties, either institution or company about